Composite and non-composite behaviors of foam-insulated concrete sandwich panels. (January 2015) - Kang, Junsuk
Abstract: The structural behaviors of foam-insulated concrete sandwich panels subjected to uniform pressure have been evaluated. This study showed that the interface conditions such as composite and non-composite had a significant effect on the response of foam-insulated concrete sandwich panels, indicating that the simulated shear tie resistance should indeed be incorporated in numerical analyses. Finite element models were developed to simulate the detailed shear resistance of connectors and the nonlinear behaviors of concrete, foam and rebar components. The models were then validated using data from static tests performed at the University of Missouri. The modeling approach used here was compatible with the American Concrete Institute (ACI) Code and existing design practices. The results of this study will therefore provide improved methodology for the analysis and design of foam-insulated sandwich panels under both static and blast loadings.